ISLAMIC DA'WAH COMMUNICATION STRATEGY IN THE DIGITAL ERA: AN ANALYSIS OF THE UTILIZATION OF SOCIAL MEDIA TO SPREAD ISLAMIC VALUES - Faustyna, Faustyna; Khairani, Leylia; Ginting, Rahmanita (Proceeding International Seminar of Islamic Studies, 2025)
This study aims to analyze the communication strategy of Islamic da'wah in the digital era by utilizing social media as the main tool for spreading Islamic values. With rapid technological development, social media has become an effective platform for communicating religious messages to various levels of society, especially the younger generation. This research uses a qualitative approach with a case study method on several social media accounts that are active in conveying Islamic da'wah. The focus of the analysis includes content strategy, interaction with followers, and creative message packaging techniques to increase the audience's appeal and understanding of Islamic values. The results of the study show that effective da'wah communication strategies on social media include the use of attractive visuals, the use of easy-to-understand language, and two-way interaction with the audience through comments and question-and-answer sessions. In addition, collaboration with Muslim influencers has also been proven to expand the reach of messages. Although social media has great potential in spreading da'wah, there are challenges such as the risk of misinformation and negative comments that need to be faced wisely. This study concludes that a creative and adaptive approach in da'wah communication on social media can strengthen the dissemination of Islamic values and their relevance in the digital era. This research also provides recommendations for da'wah practitioners to develop communication strategies that are responsive to changes in digital trends